Strategy to Increase Bank Satisfaction in the New Normal Era of Covid-19. - Ryan Firdiansyah Suryawan; Primadi Candra Susanto; Naik Henokh Parmenas; Dedi Setiadi (Institute of Computer Science (IOCS), 2021)
Customer satisfaction is a comparison of what is expected with what is received by the customer. If what is received by the customer exceeds expectations, the customer can achieve satisfaction. Conversely, if the customer's expectations are higher than what is obtained, then the customer is not satisfied. In this case the company must be able to increase satisfaction so that customers do not switch to another company. The purpose of this study is: To find out strategies that can increase customer satisfaction Bank, in the Covid-19 Era. This research method is a qualitative method with a case study approach model. Research participants were selected using a purposive technique with the help of key people. Data collection methods using interviews, observation and documents. The conclusions of the results of this study are as follows: The Bank uses the theory of Customer Satisfaction Strategy according to Rianto 2010. It is a lot of fast at the time of the year, as many people as there were in the product of up to the number of consumers in the past 19 months, like this, in the midst of the 19th century. It is still difficult for the product and service of Bank through Digital payment. Bank regularly conducts outreach activities in order to prevent transmission of COVID-19 through information media at the Bank Branch Office. We also educate employees, customers and partners to always implement a clean and healthy lifestyle protocol.